Inhibitory Effect Of Lactic Acid And Nisin On Bacterial Spoilage Of Chilled Shrimp - A. R. Shirazinejad; I. Noryati; A. Rosma; I. Darah (Zenodo, 2010)
Lactic acid alone and its combined application with nisin were evaluated for reducing population of naturally occurring microorganisms on chilled shrimp. Fresh shrimps were dipped in 0, 1.0% and 2.0% (v/v) lactic acid alone and their combined application with 0.04 (g/L/kg) nisin solution for 10 min. Total plate counts of aerobic bacteria (TPCs), Psychrotrophic counts, population of Pseudomonas spp., H2S producing bacteria and Lactic acid bacteria (LAB) on shrimps were determined during storage at 4 °C. The results indicated that total plate counts were 2.91 and 2.63 log CFU/g higher on untreated shrimps after 7 and 14 days of storage, respectively, than on shrimps treated with 2.0% lactic acid combined with 0.04 (g/L/kg) nisin. Both concentrations of lactic acid indicated significant reduction on Pseudomonas counts during storage, while 2.0% lactic acid combined with nisin indicated the highest reduction. In addition, H2S producing bacteria were more sensitive to high concentration of lactic acid combined with nisin during storage. : {"references": ["Ogden, K. And Tubb, R.S., 1985. Inhibition of Beer-Spoilage Lactic Acid\nBacteria by Nisin. J. Inst. Brew. 91, 390-392.", "Stevens, K.A., Sheldon, B.W., Klapes, N.A. and Klaenhammer, T.R.,\n1991. Nisin Treatment for Inactivation of Salmonella Species and Other\nGram-Negative Bacteria. Appl. Environ. Microbiol. 57(12), 3613- 3614.", "Sheffet, S.M., Sheldon, B.W., and Klaenhammer, T.R., 1995. Efficiency\nof Optimized Nisin-based Treatments to Inhibit Salmonella typhimurium\nand Extend Shelf life of Broiler Carcasses. J. Food Prot. 58:1077-1082.", "Taoukis, P.S., Koutsoumanis, K. and Nychas, G.J.E., 1999. Modelling for\nShell Life Control of Chilled Fish. Int. J. Food Microbiol. 53(1), 21-31.", "Ponce, E., P.L.A., R., Sendra, E., Guamis, B. and Mor-Mur, M., 1998.\nCombined Effect of Nisin and High Hydrostatic Pressure on Destruction\nof Listeria Innocua and Escherichia coli in Liquid Whole Egg. Int. J.\nFood Microbiol. 43(1-2), 15-19.", "Yuste, J., M. Mor-Mur, M. Capellas, B. Guamis, and R. P.L.A., 1998.\nMicrobiological Quality of Mechanically Recovered Poultry Meat Treated\nWith High Hydrostatic Pressure and Nisin. Food Microbiol. 15, 407-414.", "Hurst, A. and Hoover, D.G., 1993. Nisin. In Davidson, P.M. and Branen,\nA.L. (Eds). Antimicrobials In Foods. Marcel Dekker, New York: 367.", "Cleveland J., Montville T.J., Nes I.F., Chikindas M.L., 2001.\nBacteriocins: Safe, Natural Antimicrobials for Food Preservation. Int. J.\nFood Microbiol. 71:1-20.", "Thomas, L.V., Clarkson M.R. and Delves-Broughton, J., 2000. \"Nisin\", in\nNaidu A.S., Natural Food Antimicrobial Systems, CRC Press, Boca\nRaton, Florida.\n[10] APHA \"American Public Health Association\", 1984. Compendium of\nMethods for the Microbiological Examination of Foods. 2nd ed. American\nPublic Health Association, Washington, DC.\n[11] Gram, L., Trolle, G. and Huss, H.H., 1987. Detection of Specific Spoilage\nBacteria from Fish Stored at Low (0 \u00b0C) and High (20 \u00b0C) Temperatures,\nInt. J. Food Microbial. 4, 65-72.\n[12] ICMSF \"International Commission on Microbiological Specifications for\nFoods\", 1986. Microorganisms in foods. 2-Sampling for microbiological\nanalysis: principles and specific applications. University of Toronto Press,\nToronto.\n[13] Helander. 2000. Lactic Acid Permeabilizes Gram-Negative Bacteria by\nDisrupting The Outer Membrane. Appl. Environ. Microbiol. 66, 2001-\n2005.\n[14] Samelis, J., Bedie, G.K., Sofos, J.N., Belk, K.E., Scanga, J.A. and Smith,\nG.C., 2005. Combinations of Nisin with Organic Acids or Salts to Control\nListeria monocytogenes on Sliced Pork Bologna Stored at 4\u252c\u2591C in Vacuum\nPackages. LWT Food Sci. Technol. 38, 21-28.\n[15] Gram, L. and Huss, H.H., 1996. Microbiological Spoilage of Fish and\nFish Products. Int. J. Food Microbiol. 33, 121-137.\n[16] Levin, R.E., 1968. Detection and Incidence of Specific Species of\nSpoilage Bacteria on Fish. I. Methodology. Appl. Microbiol. 16: 1734-\n1737.\n[17] Gram, L., Neergaard, W.C. and Huss, H.H., 1990. The Bacteriology of\nFresh Spoiling Lake Victorian Nile Perch (Lates niloticus). Int. J. Food\nMicrobiol. 10(3-4), 303-316.\n[18] Shamshad, S.I., Kher-Un-Nisa, Riar, M., Zuberi, R. and Qadri. R.B.,\n1990. Shelf Life of Shrimp (Penaeus Merguiensis) Stored at Different\nTemperatures. J. Food Sci. 55, 1201-1205, 1242.\n[19] Chinivasagam, H.N., Bremner, A.H., Thrower, S.J. and Nottingham,\nS.M., 1996. Spoilage Pattern of Five Species of Australian Prawns:\nDeterioration Is Influenced By Environment of Capture and Mode of\nStorage. J. Aquat. Food Prod. Technol. 5, 25-50.\n[20] Gram, L., Melchiorsen, J., 1996. Interaction between Fish Spoilage\nBacteria Pseudomonas spp. and S. putrefaciens in Fish Extracts and on\nFish Tissue. Journal of Applied Bacteriology. 80:589-595.\n[21] Huis In-t Veld JH.J., 1996. Microbial and Biochemical Spoilage of Foods:\nAn Overview. Int. J. Food Microbiol. 33:1-18.\n[22] Rasmussen S.K.J, Ross T, Olley J, Mcmeekin T., 2002. A Process Risk\nModel for the Shelf Life of Atlantic Salmon Fillets. Int. J. Food\nMicrobiol. 73:47-60.\n[23] De Vuyst, L. & Vandamme, E.J., 1995. Nisin, A Lantibiotic Produced by\nLactococcus Lactis subsp. Lactis: Properties, Biosynthesis, Fermentation\nand Applications. In: Bacteriocins of Lactic Acid Bacteria: Microbiology,\nGenetics and Applications (Edited By L. De Vuyst & E.J. Vandamme).\npp. 151-221. London: Blackie Academic and Professional.\n[24] Jack R.W., Tagg J.R., Ray B., 1995. Bacteriocins of Gram-Positive\nBacteria. Microbiol. Rev. 59:171-200.\n[25] Stiles M. E., 1996. Biopreservation by Lactic Acid Bacteria. Antonie Van\nLeeuwenhoek. 70:331-45.\n[26] Rogers A.M. and Montville T.J., 1994. Quantification of Factors Which\nInfluence Nisin-s Inhibition of Clostridium Botulinum 56a in a Model\nFood System. J. Food Sci. 59:663-8.\n[27] Thomas, L.V., Wimpenny, J.W.T., 1996. Investigation of The Effect of\nCombined Variations in Temperature, pH, and NaCl Concentration on\nNisin Inhibition of Listeria Monocytogenes and Staphylococcus aureus.\nApplied and Environmental Microbiology 62, 2006-2012.\n[28] Blom H, Katla T, Hagen B.F., Axelsson L. 1997. A Model Assay to\nDemonstrate How Intrinsic Factors Affect Diffusion of Bacteriocins. Int.\nJ. Food Microbiol. 38:103-9.\n[29] Szabo E.A., Cahill M.E., 1998. The Combined Effects of Modified\nAtmosphere, Temperature, Nisin and Alta(Tm) 2341 On The Growth of\nListeria Monocytogenes. Int J Food Microbiol 43:21-31.\n[30] Delves-Broughton, J., Blackburn, P., Evans, R.J. and Hugenholtz, J.,\n1996. Applications of the Bacteriocin, Nisin, Antonie Van Leeuwenhoek\n69, 193-202."]}